Comprehensive analyses for the coagulation and macrophage-related genes to reveal their joint roles in the prognosis and immunotherapy of lung adenocarcinoma patients - Li, Zhuoqi; Yin, Zongxiu; Luan, Zupeng; Zhang, Chi; Wang, Yuanyuan; Zhang, Kai; Chen, Feng; Yang, Zhensong; Tian, Yuan (Frontiers in Immunology, 2023)
Purpose: To explore novel biomarkers related to coagulation process and tumor-associated macrophage (TAM) infiltration in LUAD, the study was designed. Methods: The macrophage M2-related genes were obtained by WGCNA (Weighted Gene Co-Expression Network Analysis) in bulk RNA-seq data, while the TAM marker genes were identified through analyzing the scRNA-seq data, and the coagulation-associated genes were gotten from MSigDB and KEGG databases. Survival analysis was performed for the intersectional genes. Then, a risk score model was constructed based on the survival-related genes for the prognosis prediction, and validated in external datasets. Results: Thirty-three coagulation and macrophage related (COMAR) genes were obtained, 19 of which were selected for the risk score model construction. Finally, 10 survival-associated genes (APOE, ARRB2, C1QB, F13A1, FCGR2A, FYN, ITGB2, MMP9, OLR1, VSIG4) were involved in the COMAR risk score model. According to the risk score, patients were divided into low-risk and high-risk groups equally, and the prognosis of patients in the high-risk group was significantly worse than that in the low-risk group. The ROC curve indicated that the risk score model had high sensitivity and specificity, which was validated in multiple external datasets. Besides, the model also had high efficacy in predicting the clinical outcomes of LUAD patients who received anti-PD-1/PD-L1 immunotherapy. Conclusions: The COMAR risk score model constructed in this study has excellent predictive value for the prognosis and immunotherapeutic clinical outcomes of patients with LUAD, which provides potential biomarkers for the treatment and prognostic prediction.